2009
DOI: 10.2214/ajr.09.2336
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal 64-MDCT for Suspected Appendicitis: The Use of Oral and IV Contrast Material Versus IV Contrast Material Only

Abstract: Patients presenting with nontraumatic abdominal pain imaged using 64-MDCT with isotropic reformations had similar characteristics for the diagnosis of appendicitis when IV contrast material alone was used and when oral and IV contrast media were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 21 publications
3
23
0
2
Order By: Relevance
“…Anderson et al demonstrated that, there is no significant difference for diagnosing appendicitis between oral and IV enhanced MDCT with only IV enhanced MDCT by using 64-slice MDCT (20). This conclusion was the same direction of our results.…”
Section: Resultssupporting
confidence: 87%
“…Anderson et al demonstrated that, there is no significant difference for diagnosing appendicitis between oral and IV enhanced MDCT with only IV enhanced MDCT by using 64-slice MDCT (20). This conclusion was the same direction of our results.…”
Section: Resultssupporting
confidence: 87%
“…CT protocols were based on the following: effective level of 50-250 mAs, 100-120 kVp, 0.625 or 1.25 collimation, 5-mm thickness reconstruction at 5-mm intervals, 0.5 or 0.75-s rotation time, and 2 cc/kg intravenous contrast agent injection after a 70 s-delay given at a rate of 2 mL/s. We did not use enteric contrast material, as the need for enteric contrast material has been questioned in relatively recent studies [32,33]. Images were acquired from the dome of the diaphragm through the pubic symphysis.…”
Section: Ct Protocolsmentioning
confidence: 99%
“…15.19 ). The need for oral contrast administration is controversial; high accuracy rates of diagnosis have been shown in patients with acute appendicitis and blunt abdominal trauma without using oral contrast in CT, as well as in oncology patients undergoing imaging follow-up (Lee et al 2006Anderson et al 2009 ;Harieaswar et al 2009 ) (Fig. 15.20 ).…”
Section: Ct and Mrimentioning
confidence: 99%